2012
DOI: 10.5830/cvja-2011-071
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cardiovascular risk factors in an urban area of Togo : a WHO STEPS-wise approach in Lome, Togo

Abstract: ObjectiveTo determine the prevalence of hypertension and other cardiovascular risk factors in the general adult population of Lome.MethodsA cross-sectional household survey was conducted in Lome from October 2009 to January 2010, which focused on hypertension and other cardiovascular risk factors in 2 000 subjects 18 years and older. The World Health Organisation’s STEPS-wise approach on non-communicable diseases was used. During the first session, blood pressure (BP) was measured on three successive occasions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 6 publications
(16 reference statements)
4
11
0
2
Order By: Relevance
“…Strong female predominance (58.56%) was found in our study. Yaméogo et al and Baragou et al also found similar frequencies in their studies, 56.8% of the hypertensive patients in Burkina Faso [14] and 55.1% of the hypertensive population in urban population in Togo [15], respectively. This dominance could be a simple mass effect or reflect greater susceptibility of the female gender to hypertension among adults.…”
Section: Discussionsupporting
confidence: 68%
“…Strong female predominance (58.56%) was found in our study. Yaméogo et al and Baragou et al also found similar frequencies in their studies, 56.8% of the hypertensive patients in Burkina Faso [14] and 55.1% of the hypertensive population in urban population in Togo [15], respectively. This dominance could be a simple mass effect or reflect greater susceptibility of the female gender to hypertension among adults.…”
Section: Discussionsupporting
confidence: 68%
“…The proportion of screen-detected cases (reported in five studies) among those with diabetes ranged from 21.3% in rural Congo (Democratic Republic) to 90% in urban Senegal 12. Sex-specific prevalence was reported in seven studies, showing higher rates in men than women in three studies11 13 14 and the reverse in four others 10 12 15 16. Two studies provided urban versus rural comparisons in the same countries, both showing urban prevalence of diabetes about twice that observed in rural settings 17 18.…”
Section: Prevalence and Incidence Of Diabetes And Obesitymentioning
confidence: 96%
“…In many West African cities, more than 25 % of adults have hypertension (76,79) . This is the case, for example, with Ouagadougou (40·2 %) (64) , St Louis (46 %) (80) , Accra (54·6) % (73) , Dakar (27·5 %) (81) and Lome (26·6 %) (82) . The independent risk factors associated with hypertension from various studies include older age,…”
Section: Hypertensionmentioning
confidence: 97%